The Influence of “Rumah Pangan Kita” (RPK) Partnership on the Income of Grocery Traders in Malang - Az Zahra, Wara' Geffa; Dina Riana, Fitria; Haryati, Novi; Sujarwo, Sujarwo (Profit: Jurnal Adminsitrasi Bisnis, 2025)
One of Perum Bulog's efforts to maintain price stability and food availability is distributing its products through the "Rumah Pangan Kita" (RPK) partnership. However, in 2022, it was recorded that most of RPK's partners would no longer run their businesses. It is suspected that this happened because the income obtained did not match the expectations of fundamental food traders. This research aims to analyze the influence of the RPK partnership factor on the income of fundamental food traders, which is calculated through Return on Asset analysis (ROA) in Malang. The sample used in this study consisted of 30 respondents and was analyzed using multiple linear regression methods. The results showed that the variables of cooperation and commitment had a significant influence on the ROA of grocery traders in Malang. Other variables do not have a significant influence. The implications of this research highlight the importance of strengthening cooperation and commitment within the RPK partnership program to improve the profitability of fundamental food traders. Moreover, the findings suggest that communication and openness, while not significantly impactful in this study, should not be overlooked but optimized as supporting factors to enhance the overall partnership effectiveness.